(untitled) (PJDOL, 2023)
The study evaluated the self-instructional materials of M.Ed level of Allama Iqbal Open University, considering eight parameters i.e. introduction, objectives, contents of units and its organizations, format, presentation style, visual materials, individualized learning, examples from daily life, summary at the end of unit and glossary. All over Pakistan 585 students, 70 tutors, 20 Unit writers and 8 Course coordinators constituted the population of the study which was taken as a sample i.e.100% sampling. Data were collected through four questionnaires. The major results of the study portrayed that introduction of units has been written clearly, provides the introductory summary of the course units and each unit objectives are relevant to M.Ed programme.